2004
DOI: 10.1037/0893-164x.18.4.362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bupropion on Depression Symptoms in a Smoking Cessation Clinical Trial.

Abstract: Bupropion is an antidepressant shown to be efficacious for smoking cessation. This study examined the short- and long-term effects of bupropion (300 mg/day for 10 weeks) versus placebo on depression symptoms among 497 smokers attempting to quit in a randomized trial of bupropion plus behavioral counseling. Depression symptoms were assessed via the Center for Epidemiological Studies Depression Scale (L. Radloff, 1977) at baseline, end of treatment, and at 6-month follow-up. Baseline nicotine dependence level wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 24 publications
(49 reference statements)
0
24
0
2
Order By: Relevance
“…Yet, the failure of some antidepressants to improve cessation rates suggests that negative affect per se is unlikely to be any more sensitive than other withdrawal symptoms as a measure of a medication's clinical efficacy for smoking cessation (Hughes et al 2004). Further emphasizing this point is the observation that bupropion was subjected to clinical trials for cessation not on the basis of its antidepressant actions but on the basis of anecdotal observations of spontaneous abstinence among depressed smokers already taking the drug as Welbutrin (Martinez-Raga et al 2003; see also Lerman et al 2004). Similarly, relief of anxiety, another common withdrawal symptom, has provided the justification for clinical trials of a few anxiolytic medications, but none has shown efficacy for smoking cessation (Benowitz and Peng 2000).…”
Section: Research On Mechanisms Of Actionmentioning
confidence: 95%
“…Yet, the failure of some antidepressants to improve cessation rates suggests that negative affect per se is unlikely to be any more sensitive than other withdrawal symptoms as a measure of a medication's clinical efficacy for smoking cessation (Hughes et al 2004). Further emphasizing this point is the observation that bupropion was subjected to clinical trials for cessation not on the basis of its antidepressant actions but on the basis of anecdotal observations of spontaneous abstinence among depressed smokers already taking the drug as Welbutrin (Martinez-Raga et al 2003; see also Lerman et al 2004). Similarly, relief of anxiety, another common withdrawal symptom, has provided the justification for clinical trials of a few anxiolytic medications, but none has shown efficacy for smoking cessation (Benowitz and Peng 2000).…”
Section: Research On Mechanisms Of Actionmentioning
confidence: 95%
“…A pesar de no estar claro su funcionamiento, el Bupropion (Zyntabac) parece aumentar los niveles de dopamina y norepinefrina actuando como antagonista de la nicotina por su capacidad para bloquear las subunidades α3β2 y α3β4 de los receptors colinérgicos nicotínicos (Lerman et al, 2004;Benowitz, 2008b;Xi, Spiller y Gardner, 2009). A igual que la terapia sustitutiva de la nicotina, el Bupropion está recomendado como fármaco de primera línea en el tratamiento del tabaquismo (Fiore et al, 2008), mostrando aproximadamente el doble de éxito en comparación con el placebo en estudios de meta-análisis (Henningfield, Fant y Buchhalter, 2005).…”
Section: Farmacología Y Estrategias Para El Ma-nejo Del Craving Por Lunclassified
“…A limitation of this study is the fact that the population of smokers had low scores of depression and therefore we don't know if cognitive-behavioral treatment for depression could be more beneficial in smokers with higher depression scores. In a previously published study it has been shown that this type of treatment is effictive only for smokers with recurrent major depression [Lerman et al 2004].…”
Section: Treatment With Other Antidepressantsmentioning
confidence: 99%